The Role of the Patent System in Stimulating Innovation and Technology Transfer for Climate Change Including Aspects of Licensing and Competition Law - Kim, Hee-Eun (Munich Intellectual Property Law Center - MIPLC, 2011)
The world increasingly faces the adverse impact of climate change. What role can intellectual property play to stimulate the necessary innovation and technology transfer? Providing an inventory of patent law, policy and information, including certain private initiatives, this thesis discusses issues at the crossroads of intellectual property and climate change, such as: compulsory licensing for climate change, patent offices